PRODUÇÃO E CARACTERIZAÇÃO BIOQUÍMICA DE L-ASPARAGINASE PRODUZIDA POR FUNGOS FILAMENTOSOS ISOLADOS DA MATA ATLÂNTICA - Groll, Simone Von (2024)
The enzyme L-asparaginase (L-asparagine amidohydrolase, EC 3.5.1.1) is widely used in the treatment of leukemias, particularly Acute Lymphoblastic Leukemia (ALL), and in the food industry to mitigate acrylamide formation. However, the L-asparaginase currently available for pharmaceutical applications of the bacterial origin, which can result in adverse effects and reduced therapeutic efficacy. Consequently, this study aimed to screen filamentous fungi isolated from a fragment of the Atlantic Forest, from western Paraná, to identify a microorganism capable of producing L-asparaginase. The screening for L-asparaginase-producing fungi was conducted using solid and liquid media methodologies. The selected fungal strain was evaluated for its enzymatic activity under varying culture conditions, including medium composition, incubation time, carbon and nitrogen sources and amino acid supplementation. A Plackett- Burman statistical design was employed to assess the influence of seven variables on L-asparaginase production, followed by optimization using a central composite rotational design( CCRD) comprising 27 trials. Additionally, the enzyme present in the crude extract was biochemically characterized to determine its optimal temperature and pH conditions. Partial purification was perfomed via size exclusion chromatography, followed by biochemical characterization of the purified enzyme. Plate screening revealed that all five evaluated fungal strains were L-asparaginase producers. Among them, Cunninghamella echinulata PA3S12MM demonstrated superior enzyme production during submerged fermentation, achieving activities of 4.79 U/mL and 2.70 U/mL in the extracellular and intracellular extracts, respectively. The Czapek culture medium was identified as the most suitable for the optimized L- asparaginase production, with maximum activity observed after 120 hours of cultivation. The optimal culture conditions were determined through Plackett-Burman design followed by CCRD optimization. Maximum enzymatic activity (7.14 U/mL) was achieved after 120 hours of cultivation at 28 °C, with supplementation of 7% glucose, 1.5% chicken feathers and 0.15% proline. The crude enzyme extract exhibited optimal activity at pH 5.0 and 60 °C. Partial enzyme purification via size exclusion chromatography and high-performance liquid chromatography (HPLC) resulted in a 10.4-fold purification factor with a recovery yield of 0.2%. The partially purified enzyme demonstrated maximum activity at pH 7.0 and 85 °C and showed stability within a pH range of 4.0-6.0, along with thermoactivation following 30 minutes of incubation at 95 °C. Beta-mercaptoethanol enhanced enzymatic activity by 72.1%. The apparent kinetic parameters for asparagine hydrolysis were determined as Km= 0.011 mmol L−1 and Vmax = 126.5 mmol L-1 min-1. In conclusion, the results highlight the C. echinulata PA3S12MM as a promising source of L-asparaginase, with potential applications in translational medicine for leukemia treatment and in the food industry for acrylamide mitigation.